Revisiting the Policy Cycle in Bangladesh: An Analytical Perspective Through Paul Cairney’s Framework - Arafat, Md. Yeasir; Tarif Hosen; Fahmida (Journal of Governance and Public Affairs, 2026)
This study examines the policymaking process in Bangladesh through Paul Cairney’s policy cycle model, which includes agenda setting, policy formulation, legitimation, implementation, evaluation, and policy maintenance, change, or termination. Based exclusively on secondary data, the study explores the extent to which this model explains policymaking practices in Bangladesh while also identifying its limitations in capturing the country’s complex political and administrative realities. In particular, it highlights challenges such as fragmented governance structures and the presence of multiple centres of authority that extend beyond the explanatory capacity of the traditional policy cycle model. The study suggests pathways for improving transparency, participation, and effectiveness in policymaking. It also underscores the need to integrate alternative theoretical perspectives to better understand the dynamic and non-linear nature of policymaking processes. Finally, the study acknowledges limitations related to secondary data usage and the evolving political context, offering directions for future research